2017
DOI: 10.1080/10428194.2017.1306647
|View full text |Cite
|
Sign up to set email alerts
|

The PARP inhibitor olaparib enhances the cytotoxicity of combined gemcitabine, busulfan and melphalan in lymphoma cells

Abstract: The combination of gemcitabine (Gem), busulfan (Bu) and melphalan (Mel) is a promising regimen for autologous stem-cell transplantation (SCT) for lymphomas. To further improve the efficacy of [Gem+Bu+Mel], we added PARP inhibitor olaparib (Ola). We hypothesized that Ola would inhibit the repair of damaged DNA caused by [Gem+Bu+Mel]. Exposure of J45.01 and Toledo cell lines to IC10–20 of individual drug inhibited proliferation by 6%–16%; [Gem+Bu+Mel] by 20%–27%; and [Gem+Bu+Mel+Ola] by 61%–67%. The synergistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…However, long-term survival of AML patients remains poor for refractory/relapse cases [44][45][46]. We hope to explore new treatments that induce DNA PARP-1 plays a pivotal role in DNA repair, particularly in response to DNA-damaging agents [47,48]. We found that PARP-1 was highly expressed in CN-AML patients and AML cell lines compared to normal BM donors.…”
Section: Discussionmentioning
confidence: 96%
“…However, long-term survival of AML patients remains poor for refractory/relapse cases [44][45][46]. We hope to explore new treatments that induce DNA PARP-1 plays a pivotal role in DNA repair, particularly in response to DNA-damaging agents [47,48]. We found that PARP-1 was highly expressed in CN-AML patients and AML cell lines compared to normal BM donors.…”
Section: Discussionmentioning
confidence: 96%
“…PARP-1 plays a pivotal role in DNA repair, particularly in response to DNA-damaging agents [47,48]. We found that PARP-1 was highly expressed in CN-AML patients and AML cell lines compared to normal BM donors.…”
Section: Discussionmentioning
confidence: 98%
“…The simultaneous occurrence of both types of cellular stress may transmit signals to the mitochondria, as suggested by the decreased mitochondrial membrane potential due to increased ROS production ( Figure 3 B). Such mitochondrial stress is triggered by DNA damage, which also induces apoptosis by phosphorylating mitochondrial proteins involved in the release of cytochrome c [ 71 ]. Metformin combined with 2.5 mM glucose upregulates cytosolic cytochrome c in SKOV3 cells and decreases mitochondrial membrane potential, suggesting that low glucose and metformin trigger cell apoptosis through the mitochondria-associated pathway [ 38 ].…”
Section: Discussionmentioning
confidence: 99%